Survival rate comparisons amongst cervical cancer patients treated with an open, robotic-assisted or laparoscopic radical hysterectomy: A five year experience - Mendivil, Alberto A.; Rettenmaier, Mark A.; Abaid, Lisa N.; Brown, John V.; Micha, John P.; Lopez, Katrina L.; Goldstein, Bram H. (Surgical oncology, 2016)
The purpose of this retrospective study was to assess the 5-year survival outcomes of cervical cancer patients who underwent an, open radical hysterectomy (ORH), robotic-assisted radical hysterectomy (RRH) or laparoscopic radical hysterectomy (LRH) for the treatment of their disease. We conducted a review of all cervical cancer patients who were managed with an ORH, RRH or LRH. Forty-nine patients were treated with LRH, 58 were managed via RRH and 39 patients underwent an ORH. The LRH (1.78 h) patients had a significantly shorter operative duration than the RRH (2.88 h) and ORH (2.39 h) subjects (p < 0.001). Blood loss was the highest in the ORH (475 cc) group (RRH = 207 cc and LRH = 312 cc) (P < 0.001). Moreover, the ORH (5.04 days) patients had a significantly longer hospital stay than the LRH (2.95 days) and RRH (2.50 day) subjects (P < 0.001). Kaplan–Meier survival analysis revealed a progression free survival (PFS) rate of 84.6% for the ORH group, 89.8% for the LRH group and 89.7% for the RRH patients (P = 0.271) at 60 months; overall survival was 92.3% for the ORH group, 95.9% for the LRH group and 96.6% for the RRH patients (P = 0.80). The results from this study suggest that, irrespective of operative approach, patients who underwent a radical hysterectomy for early stage cervical cancer attained similar 5-year disease free and overall survival outcomes. •Long-term open and endoscopic radical hysterectomy survival data are indeterminate.•Blood loss and hospital stay were greater for the open procedure patients.•Open and endoscopic radical hysterectomy patients exhibited similar survival rates.